Analisis Perilaku Konsumen Terhadap Pembelian Jamur Tiram di Kota Pekanbaru - Eka Sunarya Putri; Eliza '; Evy Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research was conducted in the city of Pekanbaru which aims to analyze the attitudes and behavior of consumers towards products of oyster mushroom in the city of Pekanbaru. The method of analysis used in this study refers to analytical techniques in the reasoned action theory, the model developed by Fishbein. Purchase product attributes oyster mushroom is the price, taste, size, texture, nutritional content, health benefits and obtained easily. In the analysis of consumer confidence towards the oyster mushroom show attributes of health benefits and nutritional content are the main factor in buying products of oyster mushrooms followed by factor of texture, flavor, size. While the results of the evaluation of substances attribute analysis are the main factor in the purchase of mushrooms followed by factor of health benefits, flavor and texture. Consumer attitudes toward the oyster mushroom is good or fairly good, its value is 23.72.  Consumer confidence shows the influence of subjective norm referent (legality of the product and all people around) there arises on purchasing decisions oyster mushrooms.  Consumer behavior in purchasing products of oyster mushrooms showed positive results the value is 710.70. This means that the purchasing of oyster mushrooms is good, personality characteristics and self-concept of consumer in placing the products of oyster mushroom are positive by the manufacturer.   Keywords: Consumer, Behavior, Attitudes, Oyster Mushrooms, Fishbein.